The isp’s role in improving intellectual property protection on the digital economy (2016)
There is now a protectionist tendency of copyright in the digital economy, driven by the cultural and creative industries, which attacks the interests, freedoms and rights of Internet users. Even though this is in response to an apparent increase in infringements and piracy, it’s also the effect of an inability of the industries to adapt to a new reality. Through this paper, we want to analyze the role of the Internet Service Providers (ISP) in this issue, as actors responsible for identifying and subsequently block allegedly infringing contents. Having said the above, this analysis will be done from the American experience, and concluding in the Canadian model as a viable solution that safeguards respect for freedoms affected.